A Comparative Study of Effectiveness of Ultrasound-Guided Transversus Abdominis Plane (TAP) Block vs Epidural Analgesia for Post-Operative Pain Relief in Lower Abdominal Surgeries - Santosh Bhagasra; Neelam Meena; Vikas Rajpurohit (Academia Anesthesiologica International, 2020)
Background: An increase in the use of regional anesthesia techniques for postoperative pain relief for analgesia following lower abdominal surgeries. Epidural anesthesia considered as the "gold standard" has been established to provide excellent analgesia as well as attenuation of neurogenic contribution to inflammation. The TAP block provides reliable somatic analgesia in lower abdominal incision surgeries. Use of ultrasound helps incorrect localization of the plane and accurate placement of the needle and catheter.Subjects and Methods:In TAP group under USG guidance 20 ml 0.2% Inj. Ropivacaine was deposited on each side of the abdominal wall. In Epidural group 10 ml of 0.2% Inj. Ropivacaine was administered at skin closure.Results:Systolic and diastolic blood pressure levels were significantly lower in group B as compared to group A (p<0.05). . VAS score was significantly higher in group B as compared to group A (P<0.05). It was observed that a significantly higher number of patients in epidural group required rescue analgesia and at higher dosages (p<0.05).Conclusion:TAP block has almost no complications, keeps the patient hemodynamically stable and offers a good early postoperative analgesia (till 24 hours) when compared to a more accepted modality like epidural analgesia.